Small Enterprise Growth and the Rural Investment Climate: Evidence from Tanzania - Kinda, Tidiane; Loening, Josef L. (2012)
This paper analyzes characteristics of nonfarm enterprises, their employment growth patterns, and constraints in doing business in rural Tanzania. Using unique survey data, we describe a low-return sector struggling to compete in a challenging business environment. However, about one-third of rural enterprises are growing fast. Most enterprises engage in agricultural trade. Due to a rapidly growing agricultural sector in recent years, limiting demand-side constraints, rural enterprise constraints in Tanzania mainly operate from the supply-side, suggesting that in particular access to finance, road infrastructure and rural cell phone communication is associated with employment growth. A major finding is that subjective and objective measurements of business constraints are broadly comparable. We discuss a number of factors that would help to unleash the full potential of private sector-led growth in rural areas. Marginal improvements of the rural investment climate matter for growth.